Financial Statements’ Quality, Interactions Between Achievement Motivation And Good University Governance (Studies at Private Universities in the city of Bandung and its surroundings) - et. al., Veronica Christina, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research was conducted on private universities in Bandung area. Educational institutions which are very important for the development of a nation are currently still experiencing obstacles, namely the weak accountability to the public in the form of financial reports. This study aims to overcome problem of private universities in Bandung by implementing good university governance (GUG) and being strengthened by employees who have high achievement motivation. This research is an explanatory study with one hundred employees of the financial department related to financial reports as a sample of the study. The study found GUG influenced financial statements’ quality, achievement motivation did not influence financial statements’ quality, and achievement motivation is proved to be a pure moderator on the relationship between GUG and financial statements’ quality. These results can be used as a consideration when recruiting employees. It is better if personality traits are tested in order to obtain employees who have the desire to excel so that they can strengthen the application of GUG in affecting the quality of financial statements.